2015
DOI: 10.1186/s12879-015-1216-1
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent skin and soft tissue infections in HIV-infected patients during a 5-year period: incidence and risk factors in a retrospective cohort study

Abstract: BackgroundSkin and soft tissue infections (SSTIs) are common in the era of community-associated methicillin resistant Staphylococcus aureus among HIV-infected patients. Recurrent infections are frequent. Risk factors for recurrence after an initial SSTI have not been well-studied.MethodsRetrospective cohort study, single center, 2005–2009. Paper and electronic medical records were reviewed by one of several physicians. Subjects with initial SSTI were followed until the time of SSTI recurrence. Standard descrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
1
5
0
1
Order By: Relevance
“…Our study also sought to evaluate the association between nasal colonization by MRSA and co-morbidities such as diabetes, chronic liver disease, cancer and sexually transmitted diseases, but was unable to establish any significant associations. Hemmige and collaborators [ 19 ] observed that none of these variables was associated with nasal colonization by MRSA. A similar study conducted in Iran stressed that there was no association between MRSA nasal colonization and cigarette smoking or prior use of antibiotics [ 5 ].…”
Section: Main Textmentioning
confidence: 99%
“…Our study also sought to evaluate the association between nasal colonization by MRSA and co-morbidities such as diabetes, chronic liver disease, cancer and sexually transmitted diseases, but was unable to establish any significant associations. Hemmige and collaborators [ 19 ] observed that none of these variables was associated with nasal colonization by MRSA. A similar study conducted in Iran stressed that there was no association between MRSA nasal colonization and cigarette smoking or prior use of antibiotics [ 5 ].…”
Section: Main Textmentioning
confidence: 99%
“…In hospitalized patients, nonadherence to oral antibiotics after discharge is an important predictor of poor outcome and relapse 13. In a community setting, adherence can be further compromised; PWID are at higher risk of recurrent ABSSSIs14 and more likely to have severe disease with adverse outcomes 15,22. Reasons for outpatient antibiotic failure in PWID also include missed follow-up visits, noncompliance with antibiotic therapy, and documented line manipulation 22.…”
Section: Discussionmentioning
confidence: 99%
“…Infectious diseases are a major health issue in PWID, who typically seek medical attention later in their disease course 13. PWID are at higher risk of recurrent ABSSSIs,7,14 necrotizing fasciitis, and infective endocarditis due to spread from skin and soft tissue abscesses into the bloodstream, and they are more likely to experience adverse outcomes associated with this disease 15,16. Medical care for patients with a history of injection drug use is complicated by medical, social, and economic issues that affect adherence 13.…”
Section: Introductionmentioning
confidence: 99%
“…One of the statistical methods used for analyzing timeto-event data in the presence of censored data is the survival analysis that is mostly used for investigating the survival and hazard rates of patients based on different covariates (10). In the survival analysis in many medical situations, patients experience recurrent events such as the development of new tumors in cancer patients, the occurrence of ischemic attacks in coronary artery disease patients, re-hospitalization, and the incidence of recurrent opportunistic infections in HIV-positive patients (11)(12)(13)(14). In the above-mentioned examples, the recurrent events of an individual are possible given the basic characteristics of the individual.…”
Section: Objectivesmentioning
confidence: 99%